Physical Education Textbook Study: Techniques and Forms of Assessment of Knowledge and Skills of Middle School Students in Indonesia - Dani Sulistiantoro; Feri Budi Setyawan (JUMORA: Jurnal Moderasi Olahraga, 2021)
This research aims to find out the form and technique of assessment on aspects of knowledge and skills in the textbooks of students of physical education sports and health (PJOK) class VIII Curriculum 2013. The instruments in this study are researchers themselves who are equipped with a set of theories and data cards that contain techniques and forms of assessment of aspects of knowledge and skills. The instrument is validated by validation of content or content by experts or expert judgement in this case done by experts. Data collection technique with a record reading technique. Data analysis techniques use Miles and Huberman's interactive model analysis techniques. This research is qualitative descriptive research. The data source in this study is the textbook of students of PJOK Class VIII Curriculum 2013. Results in this study show that not entire forms and assessment techniques on aspects of knowledge and skills exist in every chapter in the PJOK Class VIII curriculum textbook 2013. In the aspect of knowledge only uses assessment techniques in the form of multiple choices, descriptions and assignments. Assessment techniques such as right wrong, matchmaking, stuffing and Q&A have not been applied in the textbook of PJOK students curriculum class 2013. For the skill aspect only in the form of practices and products only. Project and portfolio assessment techniques have not been applied in the PJOK Class VIII Curriculum textbook 2013. After the review of the textbook PJOK Class VIII Curriculum 2013, hopefully there will be revisions in the assessment in the latest version of the 2013 Curriculum PJOK textbook that covers all variations in assessment forms and techniques in aspects of knowledge and skills. This research contributes to the importance of subsequent research on the development of variation in forms and complete assessment techniques including aspects of attitudes in PJOK.Keywords: assessment, knowledge, skill, PJOK